Biocenotic study of Huaylas, Department of Ancash - Peru - Medina Ch., Wenceslao (1992)
The biocenotic study of the Andean Zone of Huaylas represent originality the unified management of plants and animals and the influence of the various ecological and anthropogenic factors, both in the anthropocentric area and the biocenotic sector itself which comprises the essential fields of minimal human influence. Everything is made on the basis of collections of flora and fauna as well as climatological, physicochemical, ethological and diversity factors.